Propuesta de implementación de e-commerce para el hotel “gökotta” eco cabaña y resto bar campestre de Rivera- Huila (2021)
This research proposal is projected as a qualitat technique has been the analysis and bibliographicive academic study of a descriptive nature, whose main information gathering documentary review, with the general purpose of developing an electronic commerce implementation plan for the Hotel " Gökotta ”ec o cabin and country restaurant, located in the municipality of Rivera, Huila; For which it is specifically proposed to define, according to the needs and business characteristics of the organizati question, the online server that enables the developme nt of a structured commercial strategy in e on in commerce (electronic commerce), all with the objective to broaden the commercial market within the regional and national panorama of the company. Likewise, i intended to improve customer satisfaction levels, t was generating a customer loyalty strategy through the online purchase and reservation resource, being essential for this, the design and implementation of a web page linked to the electronic commerce service.